Swimming constraints and arm coordination - Seifert, L.; Chollet, D.; Rourard, A. (Human Movement Science, 2006)
Following Newell`s concept of constraint (1986), we sought to identify the constraints (organismic, environmental and task) on front crawl performance, focusing on arm coordination adaptations over increasing race paces. Forty-two swimmers (15 elite men, 15 mid-level men and 12 elite women) performed seven self-paced swim trials (race paces: as if competitively swimming 1500 m, 800 m, 400 m, 200 m, 100 m, 50 m, and maximal velocity, respectively) using the front crawl stroke. The paces were race simulations over 25 m to avoid fatigue effects. Swim velocity, stroke rate, stroke length, and various arm stroke phases were calculated from video analysis. Arm coordination was quantified in terms of an index of coordination (IdC) based on the lag time between the propulsive phases of each arm. This measure quantified three possible coordination modes in the front crawl: opposition (continuity between the two arm propulsions), catch-up (a time gap between the two arm propulsions) and superposition (an overlap of the two arm propulsions). With increasing race paces, swim velocity, stroke rate, and stroke length, the three groups showed a similar transition in arm coordination mode at the critical 200 m pace, which separated the long- and mid-pace pattern from the sprint pace pattern. The 200 m pace was also characterized by a stroke rate close to 40 stroke min-1. The finding that all three groups showed a similar adaptation of arm coordination suggested that race paces, swim velocity, stroke rate and stroke length reflect task constraints that can be manipulated as control parameters, with race paces (R2 = .28) and stroke rate (R2 = .36) being the best predictors of IdC changes. On the other hand, only the elite men reached a velocity greater than 1.8 m s-1 and a stroke rate of 50 stroke min-1. They did so using superposition of the propulsion phases of the two arms, which occurred because of the great forward resistance created when these swimmers achieved high velocity, i.e., an environmental constraint. Conversely, the elite women and mid-level men had shorter stroke lengths and maintained a time gap between the propulsions of the two arms throughout the increase in paces, with gender and expertise explaining 9% and 8.3% of the IdC changes, respectively. These results indicate that arm coordination cannot be interpreted solely from the IdC value but should be considered from the perspective of task, environmental, and organismic constraints. These constraints can serve as control parameters in experiments aimed at gaining insight into changes in arm coordination during the front crawl. In this context, catch-up coordination, which is often considered as a mistake, was seen to be an adaptation to a relative constraint.